2013
DOI: 10.1007/s12010-013-0170-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Hydrocarbon-Degrading Bacteria in the Soil Environment and Their Contribution to Bioremediation

Abstract: A real-time PCR quantification method for indigenous hydrocarbon-degrading bacteria (HDB) carrying the alkB gene in the soil environment was developed to investigate their distribution in soil. The detection limit of indigenous HDB by the method was 1 × 10(6) cells/g-soil. The indigenous HDB were widely distributed throughout the soil environment and ranged from 3.7 × 10(7) to 5.0 × 10(8) cells/g-soil, and the ratio to total bacteria was 0.1-4.3 %. The dynamics of total bacteria, indigenous HDB, and Rhodococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
11
0
3
Order By: Relevance
“…c-alkane-degrading bacteria belonging to the genus Rhodococcus isolated from their natural habitats in our previous study were closely related to R. erythropolis and strains harboring alkB R2 type [33]. Although many c-alkane-degrading…”
Section: Alkane Hydroxylase Gene-carrying Bacteria and Their Roles Inmentioning
confidence: 95%
See 1 more Smart Citation
“…c-alkane-degrading bacteria belonging to the genus Rhodococcus isolated from their natural habitats in our previous study were closely related to R. erythropolis and strains harboring alkB R2 type [33]. Although many c-alkane-degrading…”
Section: Alkane Hydroxylase Gene-carrying Bacteria and Their Roles Inmentioning
confidence: 95%
“…Moreover, alkB varies among species of the genus Rhodococcus, and oxidizable substrates differ depending on the alkB gene type [32]. For example, Fukuhara et al [33] revealed that the R. erythropolis strain NDKK6, carrying the alkB R2 type, showed a high c-alkane degradation ability. Furthermore, the carbon number of the alkyl side chain seemed to influence c-alkane degradation [34] [35] [36] [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, biodegradation of hydrocarbons occurs naturally and is found in most types of soils (Pinholt et al 1979;Whitby & Skovhus 2009). In fact, microbes which have the potential to degrade hydrocarbons are widely distributed in the environment (Bamforth & Singleton 2005;Head et al 2006;Whitby & Skovhus 2009;Fukuhara et al 2013;Boon et al 2014) and exposure to hydrocarbons result in changes in the microbial community structure. During this process, genes encoding for a variety of metabolizing enzyme are critical for the ability of microorganisms to biodegrade hydrocarbons (Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…COTBS contains a mixture of hydrocarbon fractions ranging from alkanes to polycyclic aromatic hydrocarbons (PAHs), [5] and heavy molecular weight hydrocarbons (HMWHCs) above C 40 [6]. Some fractions such as PAHs (a significant component of COTBS [7]) have carcinogenic and mutagenic characteristics to living organisms [8].…”
Section: Introductionmentioning
confidence: 99%